2021
DOI: 10.1126/scitranslmed.abj3222
|View full text |Cite
|
Sign up to set email alerts
|

Response to comment on “Genomic epidemiology of superspreading events in Austria reveals mutational dynamics and transmission properties of SARS-CoV-2”

Abstract: Further analysis of SARS-CoV-2 genome sequencing data identifies several highly recurrent genetic variants with low allele frequencies, which, if filtered out, provide estimates consistent with tighter transmission bottlenecks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Dabisch et al reported an infectious dose of 52 TCID50 for a seroconversion response and 256 TCID50 for a fever response based on an inhalation exposure of 10 minutes in non-human primates Macaques 32 . Others have estimated an infectious dose for infection ranging between single and 1000 virions based on a model combining information on viral mutations obtained through deep sequencing and epidemiology in known infector-infectee pairs 3335 . Based on the estimated relationship between E-gene RT-PCR Cq values and cell-cultured SARS-CoV-2 virus loads by Schuijt et al, the air sample which showed replication in our study contained approximately 170 000 viral copies per cubic meter of air 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Dabisch et al reported an infectious dose of 52 TCID50 for a seroconversion response and 256 TCID50 for a fever response based on an inhalation exposure of 10 minutes in non-human primates Macaques 32 . Others have estimated an infectious dose for infection ranging between single and 1000 virions based on a model combining information on viral mutations obtained through deep sequencing and epidemiology in known infector-infectee pairs 3335 . Based on the estimated relationship between E-gene RT-PCR Cq values and cell-cultured SARS-CoV-2 virus loads by Schuijt et al, the air sample which showed replication in our study contained approximately 170 000 viral copies per cubic meter of air 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Dabisch et al ( 2021 ) reported an infectious dose of 52 TCID 50 for a seroconversion response and 256 TCID 50 for a fever response based on an inhalation exposure of 10 min in nonhuman primates Macaques. Others have estimated an infectious dose for infection ranging between single and 1000 virions based on a model combining information on viral mutations obtained through deep sequencing and epidemiology in known infector-infectee pairs ( Popa et al , 2020 ; Martin and Koelle, 2021 ; Nicholson et al , 2021 ). Based on the estimated relationship between E-gene RT-PCR Cq values and cell-cultured SARS-CoV-2 virus loads by Schuijt et al ( 2021 ), the air sample which showed replication in our study contained approximately 170 000 viral copies per cubic meter of air.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple previous studies of SARS-CoV-2 within-host diversity, mutational hotspots have hampered attempts to use minor variants to track transmission of closely related lineages 11,35 , since it is difficult to distinguish hypermutable sites, recurrent artefacts, and sites that are genuinely co-transmitted. Notably, in Tonkin-Hill et al, there was no correlation between the probability of transmission between two patients and the number of minor variants they shared; samples that were epidemiologically distant from each other often had more than 10 minor variants in common.…”
Section: Discussionmentioning
confidence: 99%
“…This was true even after excluding minor variants that were generally highly prevalent in the dataset. Other authors have pointed out that automatically excluding minor variants that are present in many samples is not always warranted in epidemiological inference, for example when examining a superspreading event in which a large group of people were interacting and transmitting virus for a substantial length of time 35 . In general, it appears that convergent within-host de novo mutation is common enough to significantly complicate inferences of transmission of within-host diversity.…”
Section: Discussionmentioning
confidence: 99%